"نظام المعلومات المحاسبي لوظيفة التموين - دراسة حالة شركة دقيق سوف -" - عبد القادر, بن علي; تقي الدين, عروة; علاء الدين, وصيف بديدة (جامعة الوادي - University of Eloued, 2023)
"في ختام تقرير التربص لنظام المعلومات المحاسبي لوظيفة التموين في المؤسسة، يمكن الاستنتاج بأن هذا النظام يتمتع بعدة نقاط قوة تسهم في تحسين أداء وكفاءة وظيفة التموين. يتضمن ذلك تحسين الانتاجية، ودقة البيانات، وتحسين التحكم والرقابة، والتكامل مع الانظمة الاخرى والقدرة على الاستجابة السريعة، والامان، والحماية للمعلومات المالية. ومع ذلك فإنه ينبغي أيضا أن نأخذ في الاعتبار بعض نقاط الضعف المحتملة لوظيفة التموين. قد تواجه التحديات في التوافر المتناوب للموارد، ومشاكل التسليم والتوزيع، وإرتفاع التكاليف، والتعامل مع الموردين، والتخطيط والتنسيق ولتحسين وظيفة التموين وتعزيز فعالية نظام المعلومات المحاسبي ينبغي على المؤسسة اتخاذ إجراءات تصحيحية وتحسينية، مثل تحسين عملية التواصل والتنسيق مع الموردين، وتنظيم عمليات التسليم والتوزيع وتقديم التدريب والتطوير للموظفين، والعمل على تطوير استراتيجيات تسويق قوية وقدرة على الابتكار والتطوير من خلال تعزيز نظام المعلومات المحاسبي وتحسين وظيفة التموين، ستكون المؤسسة في موقع أفضل لتحقيق الكفاءة والتنافسية في سوق العمل. يجب أن يكون هذا التقرير توجيها لاتخاذ الاجراءات اللازمة والتحسينات التي تسهم في تطوير وظيفة التموين وتعزيز أداء المؤسسة بشكل عام." "At the conclusion of the training report for the accounting information system for the catering function in the institution, it can be concluded that this system has several strengths that contribute to improving the performance and efficiency of the catering function. This includes improving productivity, data accuracy, improving control and oversight, integration with other systems, the ability to respond quickly, and security and protection of financial information. However it should also keep in mind some potential weaknesses of the catering function. You may face challenges in the rotating availability of resources, delivery and distribution problems, high costs, dealing with suppliers, planning and coordination. Training and development of employees, and work on developing strong marketing strategies and the ability to innovate and develop by strengthening the accounting information system and improving the catering function, the institution will be in a better position to achieve efficiency and competitiveness in the labor market. This report should be a guide to take the necessary measures and improvements that contribute to the development of the catering function and enhance the performance of the institution in general."
Keywords: نظام المعلومات المحاسبي - لوظيفة التموين - دراسة حالة- شركة دقيق سوف -; Accounting information system - for the catering function - a case study - Daqiq Souf Company -